Taphonomic methods and a database to establish the origin of sedimentary silicified rocks from the Middle-recent Gravettian open-air site of La Picardie (Indre-et-Loire, France). (August 2020) - Delvigne, Vincent; Fernandes, Paul; Tuffery, Christophe; Raynal, Jean-Paul; Klaric, Laurent
Highlights: Database developed is built on the concept of evolutionary chain of silicites. Analyse is augmented by the use of taphonomic tools in order to decipher the genesis of the site. Analyse permited to understand organization of prehistoric groups through their territoriality. This contribution has profound implications for petroarchaeology and human territoriality. Abstract: For several years, multidisciplinary archaeological operations organized by the Ministry of Culture and named 'Collective Research Projects' (PCR) have enabled the design and use of a descriptive database for a part of southern and central France. This data base describes and stores the main geological aspects of sedimentary silicified rocks of chemical, biochemical or diagenetic origin (abbreviated SSR in the rest of the text) and their primary and secondary outcrops. Data were collected through a survey form describing the flint formations and using different observation grids which make up complete identity cards for each type of flint. Using their spatial attributes, these different data are linked to a shape file for flint formations, themselves digitized with ArcGIS and QGis on the basis of harmonized protocols with several layers of the WebMapService (WMS) Infoterre of the BRGM . Today, data sharing is made possible through the use of the ArcGisOnLine platform (AGOL) meeting the needs of the various users. Applied to an archaeological series, the database considers the concept of an evolutionary chain of SSR and extends an enquiry into the prehistoric relationship between SSR and their environments. According to the same criteria as those defined for the characterization of geological samples (petrology and alterology forms), it allows one to reconstruct the route traveled by any flint before its collection by prehistoric humans and then, by the use of a taphonomic form, decrypts the post-depositional SSR evolution in order to decipher the intensity and chronology of the mechanisms likely to have taken part in the sedimento-genesis of the archaeological site. In terms of understanding paleogeography, the ultimate aim of this approach, the accuracy of petro-archaeological studies is firmly established rather than being anecdotal. By demonstrating that only quantity, genetic and gitological diversity and the way in which materials from coherent geological spaces (i.e. geotopes) are introduced into the archaeological sites, allows one to discuss the method of acquisition of the materials concerned and thus to approach an understanding of the organization of prehistoric societies through their management of landscape and their relationship to territoriality. After the application of this method using the database the results are presented for particular materials coming from the Middle Gravettian series of la Picardie (Preuilly-sur-Claise, Indre-et-Loire, France).